IMPLEMENTASI MEANINGFUL LEARNING DALAM PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN UNTUK PENGEMBANGAN SPIRITUALITAS PESERTA DIDIK - Yutrimila Muada MUADA; Melna Gobel; Steviani Koikig; Jack Idrus; Afry Aui; Befry Guma; Olivianty Lombo (PT. Giat Konseling Nusantara, 2026)
This article examines the implementation of a meaningful learning approach in Christian Religious Education learning for the development of spirituality in students. From the results of the study, it was found that learning Christian Religious Education using a meaningful learning approach can help in developing students' spirituality, because meaningful learning emphasizes teaching materials connected to real experiences and students' prior knowledge, which can touch their spiritual lives so that with the right strategy it allows for spiritual development. This study was conducted to identify the implementation of meaningful learning in Christian Religious Education learning that can develop students' spirituality and analyze the effectiveness of the application of meaningful learning for the development of students' spirituality. Literature study is the method used in this study.